Design of a Free-Ruthenium In2S3 Crystalline Photosensitized Solar Cell - Byeong Sub Kwak; Younghwan Im; Misook Kang (International Journal of Photoenergy)
A new type of sulfide-based, solid-state dye material that is sensitive to visible radiation was assessed as a potential replacement for commercial ruthenium complex dyes in a dye-sensitized solar cell (DSSC) assembly. The In2S3 crystals on the surface of the TiO2 bottom blocking layer were grown as a solid-state dye material. Scanning electron microscopy of In2S3 revealed a microsized, 3D-connected sheet-like shape, which was confirmed by X-ray diffraction to be a beta-structure. The efficiency of the dye-sensitized solar cells assembled with a layer grown with In2S3 increased with increasing In2S3 mole concentrations to 0.05 M (1.02%) but decreased at concentrations greater than 0.6~0.8%. This suggests that crystalline In2S3 acts as a dye sensitized to visible radiation, but the short-circuit current density is too low compared to the commercially available ruthenium dye. This suggests that In2S3 crystals did not grow densely but were bulk-grown with large pores, resulting in a smaller amount of In2S3 per unit area. Two IPCE curves were observed, which were assigned to TiO2 and In2S3, meaning that the TiO2 surfaces were covered completely with In2S3 crystals. The exposure of TiO2 eventually leads to a reaction with the electrolytes, resulting in lower quantum efficiency.